UPAYA MENJANGKAU PASAR LEBIH LUAS PELAKU UMKM MELALUI DIGITAL MARKETING DENGAN METODE BRANDING PACKAGING MENARIK DI DESA TUNJUNGSARI - danny kurniawan; Ilham Naufal Ramadhan; Amat Sukani; Rozikin; Nurul Khasanah; Miftachul Azzahra; Khoirul Fatah; Nur Kholidah (Sekolah Tinggi Agama Islam Syubbanul Wathon Magelang, 2023)
This community service aims to increase economic value as well as reach the UMKM market through digital marketing in Tunjungsari Village, Siwalan District, Pekalongan. This community service uses explanation, discussion and practice methods. The explanation method is carried out by conveying material related to digital marketing directly to UMKM actors. Discussion method, interaction between two or more people who discuss basic knowledge. This method is to facilitate UMKM players who want to ask questions about material they don't understand. The practical method of applying it is by applying the knowledge that is already owned, namely by using tiktok marketing media as a means of product marketing. The results of this community service show that efforts to increase economic value and reach a wider market for MSMEs through digital marketing in Tunjungsari Village are focused on 5 things, namely helping problems, the importance of branding and business legality, product packaging, catalogs and attractive advertisements.